x + y + x + y + x + y + … = 7
If y = 2 , then what is the value of x ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can you prove that the nested function converges?
since 9 = +3 or -3, I think there should be two solutions. 46 and 52
Log in to reply
I also got 52 as the other answer but i think that the square root sign is conventionally used to give positive result.
Log in to reply
No, both the signs in a squareroot are correct according to maths. And its wrong to neglect the negetive result.
In some cases we neglect one result in a squareroot to take it as a measure of physical quantity. But it doesnt make sense that the other esult was wrong. It actually how we resolve the meaning of how the other can be right. (Got this answer actually from a lecture of a yale university professor who actually proved that why in some cases we get two answers as a part of squareroot. He proved both will always be correct. )
Log in to reply
@Vivek Vijayan – Thanks. I have edited it.
@Vivek Vijayan – When you are taking radical (i.e square root) , then x = ∣ x ∣
Thanks Nihar, I have edited it.
Thanks for informing, I have edited it.
In response to challenge master: Sorry @Calvin Lin sir, I'd come across, radicals of the form a + a + a + . . . . , a + b a + b a + b . . . . , a − b a − b a − b . . . . and few more.
Can you help me in proving it please?
just wanna ask how do you answer this? sqrt(2+sqrt(2+sqrt(2+.....)))=?
Log in to reply
Log in to reply
it's sqrt(2 + sqrt(2 + sqrt(2 + ....)))=?
Log in to reply
@Caeo Tan – Ohh, okay, here the solution.
2 + 2 + 2 + . . . . = x
2 + x = x
2 + x = x 2
x 2 − x − 2 = 0
Therefore, x has two values,
i.e, 2 1 + 9 or, 2 1 − 9
Of which the second one is negative so we can ignore it.
Log in to reply
@Sravanth C. – what if it's sqrt(2 + sqrt(2 - sqrt(2 + sqrt(2 - ....))))=?
Log in to reply
@Caeo Tan – 2 + 2 − 2 + 2 − . . . . = x
2 + 2 − x = x
2 + 2 − x = x 2
x 2 − 2 = 2 − x
[ x 2 − 2 ] 2 = 2 − x
x 4 + 4 − 4 x 2 = 2 − x
x 4 + 2 + x − 4 x 2 = 0
Solving the equation above we get four values for x ,
i.e, 2 1 + 5 , 1 , − 2 and 2 1 − 5
⌣ ¨
@Caeo Tan – Please see that there was a mistake in calculation, in the last question.
@Sravanth C. – What does these negative solutions signify in geometry?
How u got 7 by putting y=2...
Log in to reply
Please go through the question once again, it's hidden somewhere ⌣ ¨
No there should be only 1solution X=49-√9 is a 1 degree equation so only 1 soln. Consider x=√9 so x=3 and not -3 ....hard to absorb ...but it is the fact
Given this equation:
x + y + x + y + x + y + … = 7
We can square both sides of the equation: x + y + x + y + x + y + … = 7 2 = 4 9
Subtract x from both sides:
y + x + y + x + y + … = 4 9 − x
Square both sides again:
y + x + y + x + y + … = ( 4 9 − x ) 2
Refer back to our original equation (the position of the ellipses does not matter, as both continue forever and converge to 7): x + y + x + y + x + y + … = 7
Substitute 7 for the nested square root: y + 7 = ( 4 9 − x ) 2
This is a good time to substitute given y = 2 : 2 + 7 = ( 4 9 − x ) 2 9 = ( 4 9 − x ) 2 ± 3 = 4 9 − x 4 9 − x = − 3 O R 4 9 − x = 3 x = 4 9 + 3 O R x = 4 9 − 3 x = 5 2 O R x = 4 6
y=2. So, sqrt(x + sqrt(2 + sqrt(x +...))) = 7
we see that sqrt(x+...) inside the expression on the left is 7.
So, sqrt(x + (sqrt(2 + 7))) = 7
doing algebra
x + sqrt(9) = 49 x + 3 = 49 x = 46
Good solution @Ador El , but it would be better if you had used L A T E X ,learn more about it here .
sqrt(x+sqrt(2+7))=7||sqrt(x+3)=7|| x+3=49||x=46
Good solution @Caeo Tan sir, but it would have been better if you'd used L A T E X learn more about it here .
Problem Loading...
Note Loading...
Set Loading...
According to the question, x + y + x + y + x + y + … = 7
Substituting, y = 2 in the equation, we get, x + 2 + x + 2 + x + 2 + … = 7
Or, x + 2 + 7 = 7
Squaring both the sides, x + 9 = 7 2 x + 3 = 4 9 x = 4 9 − 3 x = 4 6
Or, by taking 9 as negitve, we get x = 5 2 as the new result, because the problem poser has given 4 6 as the answer